An Omni‐healable and Tailorable Aqueous Lithium‐Ion Battery. Issue 4 (14th December 2017) - Hao, Zhaohan; Tao, Feng; Wang, Zhikui; Cui, Ximing; Pan, Qinmin
Abstract: Reliability and safety are critical issues for portable power sources aiming for next‐generation electronics. However, most lithium‐ion batteries (LIBs) will fail to work or will cause safety problems after physical damage or violent deformation. Here, an omni‐healable aqueous LIB, which can self‐repair its electrodes and electrolyte simultaneously after mechanical breakage, is fabricated by integrating all of the electroactive components into polymer networks cross‐linked by dynamic borate ester bonding. Once suffering from repeated cutoffs, the battery quickly recovers its configuration integrity as well as mechanical and electrochemical properties autonomously without external stimuli. Furthermore, the battery can also be tailored into complicated patterns while maintaining its lithium‐storage properties. The present investigation offers a strategy to design a smart and sustainable energy‐storage device that has potential applications in wearable/flexible electronics, flexible robot or intelligent apparel, and so on. Abstract : Self‐help : An omni‐healable aqueous lithium‐ion battery, fabricated by integrating all of the electroactive components into polymer networks cross‐linked through dynamic borate ester bonding, can self‐repair its electrodes and electrolyte simultaneously after mechanical breakage. It can also be tailored into complicated patterns without significant deterioration in lithium‐storage properties.